A wear-resistant bright silver three-dimensional heat transfer film and a preparation process thereof
Patent Information
- Application Number
- CN202511124779.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-08-12
AI Technical Summary
现有技术中,传统热转印膜常因保护层结构设计单一、填料分散性差或固化工艺复杂,导致耐磨性能不足、光泽保持性欠佳,且立体亮银效果易因摩擦或环境因素受损
本发明以聚(偏二氟乙烯-共-六氟丙烯)、邻苯二甲酸二丁酯为原料,在离型层表面先构建具有多孔结构的基体树脂作为复合填料填充的框架,接着将光引发剂接枝在低聚倍半硅氧烷表面,得到含有光引发剂、甲基丙烯酰氧基丙基活性官能团的复合填料,将其以适当的用量滴加在多孔树脂基体中进行填充,并进一步光固化形成保护层。优势在于无需额外添加其他助剂、光引发剂或热固化,光固化操作方便快捷,大大提高生产效率,降低生产成本。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of heat transfer film technology, specifically a wear-resistant bright silver three-dimensional heat transfer film and its preparation process. Background Technology
[0002] In the field of heat transfer film technology, with the increasing demands of the consumer market for the decorative and functional aspects of products, the development of heat transfer films that combine high wear resistance, gloss, and three-dimensional visual effects has become an industry trend. In existing technologies, traditional heat transfer films often suffer from insufficient wear resistance and poor gloss retention due to simple protective layer structure design, poor filler dispersion, or complex curing processes. Furthermore, the three-dimensional bright silver effect is easily damaged by friction or environmental factors.
[0003] Therefore, how to prepare a heat transfer film with stable structure, excellent wear resistance and a bright silver three-dimensional bright silver effect by optimizing the film structure, improving the filler composite process and curing technology is a technical problem that urgently needs to be solved. Summary of the Invention
[0004] The purpose of this invention is to provide a wear-resistant bright silver three-dimensional heat transfer film and its preparation process, so as to solve the problems raised in the prior art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: A wear-resistant bright silver three-dimensional heat transfer film, wherein the heat transfer film structure comprises, from top to bottom, a PET base film, a release layer, a color printing layer, a protective layer, an aluminum plating layer, a screen printing embossed layer, and an adhesive layer. Furthermore, the protective layer is prepared by photoinitiator-modified POSS filler and porous resin substrate through ultraviolet light curing; Furthermore, the preparation method of the photoinitiator-modified POSS filler includes the following steps: S1: Add hydroxyethyl acrylate, 3-mercaptopropyltrimethoxysilane and triethylamine into a reaction vessel, heat to 65-70℃ and react for 8-12 hours, then cool to room temperature to obtain a hydroxysilane coupling agent; Furthermore, in the preparation process of the hydroxysilane coupling agent, the molar ratio of hydroxyethyl acrylate: 3-mercaptopropyltrimethoxysilane: triethylamine is (0.022-0.064):(0.022-0.064):(0.0001-0.0003); S2: 3-(methacryloyloxy)propyltrimethoxysilane, hydroxysilane coupling agent, 10wt% tetramethylammonium hydroxide aqueous solution, and isopropanol were added to a reaction vessel, heated to 45-50℃ and stirred for 48h, rotary evaporated, toluene was added to dissolve the product, washed with saturated brine until neutral, dried with anhydrous magnesium sulfate, and concentrated to obtain a composite hydrolytic coupling agent; the composite hydrolytic coupling agent was added to a 15wt% toluene solution containing tetramethylammonium hydroxide and triethylamine, and refluxed under a nitrogen atmosphere for 72h to obtain hydroxy-methacryloyloxypropyl oligomeric silsesquioxane; Furthermore, in the preparation process of the composite hydrolytic coupling agent, the molar ratio of 3-(methacryloyloxy)propyltrimethoxysilane to hydroxysilane coupling agent is (6-7):(1-2); Furthermore, in the preparation process of hydroxy-methacryloxypropyl oligomeric silsesquioxane, the mass ratio of the composite hydrolytic coupling agent to the toluene solution containing tetramethylammonium hydroxide and triethylamine is (45-50):(6-7); in the toluene solution containing tetramethylammonium hydroxide and triethylamine, the mass ratio of tetramethylammonium hydroxide to triethylamine is 1:1. S3: Add lithium wire and trimethylchlorosilane to tetrahydrofuran, cool to -78℃, add tetrahydrofuran solution of germanium chloride for 1-1.5h, stir at room temperature for 24-25h, filter with diatomaceous earth, add the filtrate to 10v / v% hydrochloric acid, filter, extract with diethyl ether, dry, rotary evaporate, and crystallize with acetonitrile to obtain tetra(trimethylsilyl)germanane; Furthermore, in the preparation of tetra(trimethylsilyl)germanane, the mass ratio of trimethylchlorosilane:lithium wire:germanium chloride is 69.4:10:31.1; S4: Add tetra(trimethylsilyl)germanium and potassium tert-butoxide to ethylene glycol dimethyl ether and stir until homogeneous. Add 2,4,6-trimethylbenzoyl fluoride in three equal portions, stirring until homogeneous after each addition. After the addition is complete, stir the reaction for 30-45 minutes to obtain potassium tri(2,4,6-trimethylbenzoyl)germanium. Furthermore, in the preparation of potassium tris(2,4,6-trimethylbenzoyl)germanide, the molar ratio of tetra(trimethylsilyl)germanane: potassium tert-butoxide: 2,4,6-trimethylbenzoyl fluoride is 1:1:3; S5: Add 1,2-dibromoethane to tetrahydrofuran, cool to -70°C, add potassium tris(2,4,6-trimethylbenzoyl)germanide to tetrahydrofuran, stir to room temperature, remove solvent under vacuum, resuspend the product in toluene, filter, and purify to obtain tris(2,4,6-trimethylbenzoyl)germanide bromide; Furthermore, in the preparation of tris(2,4,6-trimethylbenzoyl)germanium, the equivalence ratio of potassium tris(2,4,6-trimethylbenzoyl)germanium to 1,2-dibromoethane is 5.5:1; S6: Hydroxy-methacryloxypropyl oligomeric silsesquioxane was added to a tetrahydrofuran solution of tribromotris(2,4,6-trimethylbenzoyl)germanane, and excess diisopropylethylamine was added. The mixture was heated to 60-65℃ and reacted for 24 hours under a nitrogen atmosphere in the dark. The product was washed with tetrahydrofuran and toluene to obtain photoinitiator modified POSS filler. Furthermore, in the preparation of photoinitiator-modified POSS filler, the equivalent ratio of hydroxy-methacryloyloxypropyl oligomeric silsesquioxane to brominated tris(2,4,6-trimethylbenzoyl)germanane is 1:(1-2).
[0006] A process for preparing a wear-resistant bright silver three-dimensional heat transfer film includes the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6-8 g / m². 2 The dry coating weight is 1.6-1.8 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add poly(vinylidene fluoride-co-hexafluoropropylene) and dibutyl phthalate to acetone, heat to 50-55℃ and stir evenly. Coat the mixture on the surface of the color printing layer, air dry for 5-10 minutes, wash with anhydrous ethanol to obtain a porous resin substrate; add photoinitiator modified POSS filler to dimethyl carbonate, stir evenly, drop the mixture onto the porous resin substrate, air dry in the dark for 8-12 hours, purge with nitrogen for 10-15 minutes, and cure with ultraviolet light under nitrogen atmosphere for 10-15 minutes to obtain a protective layer; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0007] Furthermore, in the preparation process of the porous resin substrate, the mass ratio of poly(vinylidene fluoride-co-hexafluoropropylene): dibutyl phthalate is 1:(5-15).
[0008] Furthermore, during the preparation of the protective layer, the amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate was 3.22-3.46 g / m². 2 .
[0009] Furthermore, the parameters of the poly(vinylidene fluoride-co-hexafluoropropylene) are: Mw is 400 kDa, and density at 25°C is 1.77 g / cm³. 3 .
[0010] Furthermore, the thickness of the protective layer is 10-40 μm.
[0011] Compared with the prior art, the beneficial effects of the present invention are: This invention uses poly(vinylidene fluoride-co-hexafluoropropylene) and dibutyl phthalate as raw materials. A porous matrix resin is first constructed on the release layer surface as a framework for the composite filler. Then, a photoinitiator is grafted onto the surface of an oligomeric silsesquioxane to obtain a composite filler containing the photoinitiator and methacryloxypropyl active functional groups. This filler is then added dropwise to the porous resin matrix in an appropriate amount for filling, and further photocured to form a protective layer. The advantages are that no additional additives, photoinitiators, or thermosetting agents are required; the photocuring operation is convenient and quick, greatly improving production efficiency and reducing production costs. Detailed Implementation
[0012] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0013] Example 1: A preparation process for a wear-resistant bright silver three-dimensional heat transfer film, comprising the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6 g / m². 2 The dry coating weight is 1.6 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add 0.1g of poly(vinylidene fluoride-co-hexafluoropropylene) and 0.5g of dibutyl phthalate to 10g of acetone, heat to 50℃ and stir until homogeneous. Coat the mixture onto the surface of the color printing layer, air dry for 5 minutes, and wash with anhydrous ethanol to obtain a porous resin substrate. Add photoinitiator-modified POSS filler to dimethyl carbonate, stir until homogeneous, and drop the mixture onto the porous resin substrate. Air dry in the dark for 8 hours, purge with nitrogen for 10 minutes, and cure under ultraviolet light in a nitrogen atmosphere for 10 minutes to obtain a protective layer. The amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate is 3.22g / m. 2 ; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0014] The preparation method of the photoinitiator-modified POSS filler includes the following steps: S1: 0.064 mol of hydroxyethyl acrylate, 0.064 mol of 3-mercaptopropyltrimethoxysilane, and 0.0003 mol of triethylamine were added to a reaction vessel, heated to 65°C and reacted for 8 hours. The mixture was then cooled to room temperature to obtain a hydroxysilane coupling agent. S2: 6 mol of 3-(methacryloyloxy)propyltrimethoxysilane, 2 mol of hydroxysilane coupling agent, 10 wt% tetramethylammonium hydroxide aqueous solution, and isopropanol were added to a reaction vessel, heated to 45°C and stirred for 48 h, rotary evaporated, toluene was added to dissolve the product, washed with saturated brine until neutral, dried with anhydrous magnesium sulfate, and concentrated to obtain a composite hydrolytic coupling agent; 45 g of the composite hydrolytic coupling agent was added to 6 g of 15 wt% toluene solution containing tetramethylammonium hydroxide and triethylamine, and refluxed under a nitrogen atmosphere for 72 h to obtain hydroxy-methacryloyloxypropyl oligomeric silsesquioxane; S3: Add 10g lithium wire and 69.4g trimethylchlorosilane to tetrahydrofuran, cool to -78℃, add 31.1g tetrahydrofuran solution of germanium chloride after 1h, stir at room temperature for 24h, filter with diatomaceous earth, add the filtrate to 10v / v% hydrochloric acid, filter, extract with diethyl ether, dry, rotary evaporate, and crystallize with acetonitrile to obtain tetra(trimethylsilyl)germanane; S4: Add 1 mmol of tetra(trimethylsilyl)germanium and 1 mmol of potassium tert-butoxide to ethylene glycol dimethyl ether and stir until homogeneous. Then add 3 mmol of 2,4,6-trimethylbenzoyl fluoride in three equal portions, stirring until homogeneous after each addition. After the addition is complete, stir the reaction for 30 min to obtain potassium tri(2,4,6-trimethylbenzoyl)germanium. S5: Add 1 equivalent of 1,2-dibromoethane to tetrahydrofuran, cool to -70°C, add 5.5 equivalents of potassium tris(2,4,6-trimethylbenzoyl)germanide in tetrahydrofuran, stir to room temperature, remove the solvent under vacuum, resuspend the product in toluene, filter, and purify to obtain tris(2,4,6-trimethylbenzoyl)germanide bromide; S6: Add 1 equivalent of hydroxy-methacryloyloxypropyl oligomeric silsesquioxane to 2 equivalents of tribromotris(2,4,6-trimethylbenzoyl)germanane in a tetrahydrofuran solution, add excess diisopropylethylamine, and react at 60-65℃ for 24 h under a light-protected, nitrogen atmosphere. Wash the product with tetrahydrofuran and toluene to obtain photoinitiator-modified POSS filler.
[0015] Example 2: A preparation process for a wear-resistant bright silver three-dimensional heat transfer film, comprising the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6 g / m². 2 The dry coating weight is 1.6 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add 0.1g of poly(vinylidene fluoride-co-hexafluoropropylene) and 1g of dibutyl phthalate to 10g of acetone, heat to 50℃ and stir evenly. Coat the mixture onto the surface of the color printing layer, air dry for 5min, and wash with anhydrous ethanol to obtain a porous resin substrate. Add photoinitiator-modified POSS filler to dimethyl carbonate, stir evenly, drop the mixture onto the porous resin substrate, air dry in the dark for 8h, purge with nitrogen for 10min, and cure with ultraviolet light under a nitrogen atmosphere for 10min to obtain a protective layer. The amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate is 3.22g / m. 2 ; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0016] The remaining steps are the same as in Example 1.
[0017] Example 3: A process for preparing a wear-resistant bright silver three-dimensional heat transfer film, comprising the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6 g / m². 2 The dry coating weight is 1.6 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add 0.1g of poly(vinylidene fluoride-co-hexafluoropropylene) and 1.5g of dibutyl phthalate to 10g of acetone, heat to 50℃ and stir until homogeneous. Coat the mixture onto the surface of the color printing layer, air dry for 5 minutes, and wash with anhydrous ethanol to obtain a porous resin substrate. Add photoinitiator-modified POSS filler to dimethyl carbonate, stir until homogeneous, and drop the mixture onto the porous resin substrate. Air dry in the dark for 8 hours, purge with nitrogen for 10 minutes, and cure under ultraviolet light in a nitrogen atmosphere for 10 minutes to obtain a protective layer. The amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate is 3.22g / m. 2 ; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0018] The remaining steps are the same as in Example 1.
[0019] Example 4: A process for preparing a wear-resistant bright silver three-dimensional heat transfer film, comprising the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6 g / m². 2 The dry coating weight is 1.6 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add 0.1g of poly(vinylidene fluoride-co-hexafluoropropylene) and 1.5g of dibutyl phthalate to 10g of acetone, heat to 50℃ and stir evenly. Coat the mixture onto the surface of the color printing layer, air dry for 5min, and wash with anhydrous ethanol to obtain a porous resin substrate. Add photoinitiator-modified POSS filler to dimethyl carbonate, stir evenly, drop the mixture onto the porous resin substrate, air dry in the dark for 8h, purge with nitrogen for 10min, and cure with ultraviolet light under a nitrogen atmosphere for 10min to obtain a protective layer. The amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate is 3.46g / m. 2 ; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0020] The remaining steps are the same as in Example 1.
[0021] Example 5: A preparation process for a wear-resistant bright silver three-dimensional heat transfer film, comprising the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6 g / m². 2 The dry coating weight is 1.6 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add 0.1g of poly(vinylidene fluoride-co-hexafluoropropylene) and 1.5g of dibutyl phthalate to 10g of acetone, heat to 50℃ and stir evenly. Coat the mixture onto the surface of the color printing layer, air dry for 5min, and wash with anhydrous ethanol to obtain a porous resin substrate. Add photoinitiator-modified POSS filler to dimethyl carbonate, stir evenly, drop the mixture onto the porous resin substrate, air dry in the dark for 8h, purge with nitrogen for 10min, and cure with ultraviolet light under a nitrogen atmosphere for 10min to obtain a protective layer. The amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate is 3.46g / m. 2 ; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0022] The preparation method of the photoinitiator-modified POSS filler includes the following steps: S1: 0.064 mol of hydroxyethyl acrylate, 0.064 mol of 3-mercaptopropyltrimethoxysilane, and 0.0003 mol of triethylamine were added to a reaction vessel, heated to 65°C and reacted for 8 hours. The mixture was then cooled to room temperature to obtain a hydroxysilane coupling agent. S2: 7 mol of 3-(methacryloyloxy)propyltrimethoxysilane, 1 mol of hydroxysilane coupling agent, 10 wt% tetramethylammonium hydroxide aqueous solution, and isopropanol were added to a reaction vessel, heated to 45°C and stirred for 48 h, rotary evaporated, toluene was added to dissolve the product, washed with saturated brine until neutral, dried with anhydrous magnesium sulfate, and concentrated to obtain a composite hydrolytic coupling agent; 45 g of the composite hydrolytic coupling agent was added to 6 g of 15 wt% toluene solution containing tetramethylammonium hydroxide and triethylamine, and refluxed under a nitrogen atmosphere for 72 h to obtain hydroxy-methacryloyloxypropyl oligomeric silsesquioxane; S3: Add 10g lithium wire and 69.4g trimethylchlorosilane to tetrahydrofuran, cool to -78℃, add 31.1g tetrahydrofuran solution of germanium chloride after 1h, stir at room temperature for 24h, filter with diatomaceous earth, add the filtrate to 10v / v% hydrochloric acid, filter, extract with diethyl ether, dry, rotary evaporate, and crystallize with acetonitrile to obtain tetra(trimethylsilyl)germanane; S4: Add 1 mmol of tetra(trimethylsilyl)germanium and 1 mmol of potassium tert-butoxide to ethylene glycol dimethyl ether and stir until homogeneous. Then add 3 mmol of 2,4,6-trimethylbenzoyl fluoride in three equal portions, stirring until homogeneous after each addition. After the addition is complete, stir the reaction for 30 min to obtain potassium tri(2,4,6-trimethylbenzoyl)germanium. S5: Add 1 equivalent of 1,2-dibromoethane to tetrahydrofuran, cool to -70°C, add 5.5 equivalents of potassium tris(2,4,6-trimethylbenzoyl)germanide in tetrahydrofuran, stir to room temperature, remove the solvent under vacuum, resuspend the product in toluene, filter, and purify to obtain tris(2,4,6-trimethylbenzoyl)germanide bromide; S6: Add 1 equivalent of hydroxy-methacryloyloxypropyl oligomeric silsesquioxane to 1 equivalent of tribromotris(2,4,6-trimethylbenzoyl)germanane in a tetrahydrofuran solution, add excess diisopropylethylamine, and react at 60-65℃ for 24 h under a light-protected, nitrogen atmosphere. Wash the product with tetrahydrofuran and toluene to obtain photoinitiator-modified POSS filler.
[0023] Comparative Example 1: A preparation process for a wear-resistant bright silver three-dimensional heat transfer film, comprising the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6 g / m². 2 The dry coating weight is 1.6 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add the photoinitiator-modified POSS filler to dimethyl carbonate, stir evenly, coat it onto the surface of the color printing layer, dry in the dark and ventilated environment for 8 hours, purge with nitrogen for 10 minutes, and cure under ultraviolet light in a nitrogen atmosphere for 10 minutes to obtain a protective layer; wherein, the amount of photoinitiator-modified POSS filler added to the porous resin substrate surface is 3.22 g / m 2 ; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0024] Comparative Example 2: A preparation process for a wear-resistant bright silver three-dimensional heat transfer film, comprising the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6 g / m². 2 The dry coating weight is 1.6 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add 0.1g of poly(vinylidene fluoride-co-hexafluoropropylene) and 2g of dibutyl phthalate to 10g of acetone, heat to 50℃ and stir until homogeneous. Coat the mixture onto the surface of the color printing layer, air dry for 5 minutes, and wash with anhydrous ethanol to obtain a porous resin substrate. Add photoinitiator-modified POSS filler to dimethyl carbonate, stir until homogeneous, and drop the mixture onto the porous resin substrate. Air dry in the dark for 8 hours, purge with nitrogen for 10 minutes, and cure under ultraviolet light in a nitrogen atmosphere for 10 minutes to obtain a protective layer. The amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate is 3.22g / m. 2 ; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0025] Comparative Example 3: A preparation process for a wear-resistant bright silver three-dimensional heat transfer film, comprising the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6 g / m². 2 The dry coating weight is 1.6 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add 0.1g of poly(vinylidene fluoride-co-hexafluoropropylene) and 0.5g of dibutyl phthalate to 10g of acetone, heat to 50℃ and stir until homogeneous. Coat the mixture onto the surface of the color printing layer, air dry for 5 minutes, and wash with anhydrous ethanol to obtain a porous resin substrate. Add photoinitiator-modified POSS filler to dimethyl carbonate, stir until homogeneous, and drop the mixture onto the porous resin substrate. Air dry in the dark for 8 hours, purge with nitrogen for 10 minutes, and cure under ultraviolet light in a nitrogen atmosphere for 10 minutes to obtain a protective layer. The amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate is 4.22g / m. 2 ; Step (4): Apply aluminum plating to the surface of the color printing layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
[0026] Experiment: Hardness performance test: Nanoscale hardness was measured using a nanoindenter.
[0027] Contact angle test: Apply a constant pressure of 50 kPa to the surface of the heat transfer film with steel wool and rub it back and forth 100 times to test the contact angle of the surface.
[0028] The experimental data are shown in Table 1 below.
[0029] Table 1 Performance Test Data of Thermal Transfer Film
[0030] Conclusion: The heat transfer film prepared by this invention has excellent wear resistance.
[0031] In Comparative Example 1, the lack of a porous resin matrix and the direct coating of photoinitiator-modified POSS filler on the surface to form a protective layer resulted in reduced wear resistance and easy detachment, as well as reduced hardness.
[0032] In Comparative Example 2, the addition of excessive dibutyl phthalate resulted in excessively large pores in the prepared porous resin matrix, uneven filling of the photoinitiator-modified POSS filler, and difficulty in filling it fully, leading to a reduction in wear resistance.
[0033] Comparative Example 3 showed that adding excessive photoinitiator to modify the POSS filler resulted in uneven dispersion and decreased light transmittance, making it unsuitable for practical application.
[0034] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A wear-resistant bright silver three-dimensional heat transfer film, characterized in that: The heat transfer film structure, from top to bottom, includes a PET base film, a release layer, a color printing layer, a protective layer, an aluminum plating layer, a screen printing embossed layer, and an adhesive layer. The protective layer is prepared by photoinitiator-modified POSS filler and porous resin substrate through ultraviolet light curing; The preparation method of the photoinitiator-modified POSS filler includes the following steps: S1: Add lithium wire and trimethylchlorosilane to tetrahydrofuran, cool to -78℃, add tetrahydrofuran solution of germanium chloride for 1-1.5h, stir at room temperature for 24-25h, filter with diatomaceous earth, add the filtrate to 10v / v% hydrochloric acid, filter, extract with diethyl ether, dry, rotary evaporate, and crystallize with acetonitrile to obtain tetra(trimethylsilyl)germanane; S2: Add tetra(trimethylsilyl)germanium and potassium tert-butoxide to ethylene glycol dimethyl ether and stir until homogeneous. Add 2,4,6-trimethylbenzoyl fluoride in three equal portions, stirring until homogeneous after each addition. After the addition is complete, stir the reaction for 30-45 minutes to obtain potassium tri(2,4,6-trimethylbenzoyl)germanium. S3: Add 1,2-dibromoethane to tetrahydrofuran, cool to -70°C, add potassium tris(2,4,6-trimethylbenzoyl)germanide to tetrahydrofuran, stir to room temperature, remove solvent under vacuum, resuspend the product in toluene, filter, and purify to obtain tris(2,4,6-trimethylbenzoyl)germanide bromide; S4: Add hydroxyethyl acrylate, 3-mercaptopropyltrimethoxysilane and triethylamine into a reaction vessel, heat to 65-70℃ and react for 8-12 hours, then cool to room temperature to obtain a hydroxysilane coupling agent; S5: 3-(methacryloyloxy)propyltrimethoxysilane, hydroxysilane coupling agent, 10wt% tetramethylammonium hydroxide aqueous solution, and isopropanol were added to a reaction vessel, heated to 45-50℃ and stirred for 48h, rotary evaporated, toluene was added to dissolve the product, washed with saturated brine until neutral, dried with anhydrous magnesium sulfate, and concentrated to obtain a composite hydrolytic coupling agent; the composite hydrolytic coupling agent was added to a 15wt% toluene solution containing tetramethylammonium hydroxide and triethylamine, and refluxed under a nitrogen atmosphere for 72h to obtain hydroxy-methacryloyloxypropyl oligomeric silsesquioxane; S6: Hydroxy-methacryloxypropyl oligomeric silsesquioxane was added to a tetrahydrofuran solution of tribromotris(2,4,6-trimethylbenzoyl)germanane, and excess diisopropylethylamine was added. The mixture was heated to 60-65℃ and reacted for 24 h under a light-protected, nitrogen atmosphere. The product was washed with tetrahydrofuran and toluene to obtain photoinitiator-modified POSS filler.
2. The wear-resistant bright silver three-dimensional heat transfer film according to claim 1, characterized in that: In the preparation of photoinitiator modified POSS filler, the equivalent ratio of hydroxy-methacryloyloxypropyl oligomeric silsesquioxane to brominated tris(2,4,6-trimethylbenzoyl)germanane is 1:(1-2).
3. The wear-resistant bright silver three-dimensional heat transfer film according to claim 2, characterized in that: In the preparation of the composite hydrolytic coupling agent, the molar ratio of 3-(methacryloyloxy)propyltrimethoxysilane to hydroxysilane coupling agent is (6-7):(1-2); In the preparation of hydroxy-methacryloxypropyl oligomeric silsesquioxane, the mass ratio of the composite hydrolytic coupling agent to the toluene solution containing tetramethylammonium hydroxide and triethylamine is (45-50):(6-7); in the toluene solution containing tetramethylammonium hydroxide and triethylamine, the mass ratio of tetramethylammonium hydroxide to triethylamine is 1:
1.
4. The wear-resistant bright silver three-dimensional heat transfer film according to claim 3, characterized in that: In the preparation of hydroxysilane coupling agents, the molar ratio of hydroxyethyl acrylate: 3-mercaptopropyltrimethoxysilane: triethylamine is (0.022-0.064):(0.022-0.064):(0.0001-0.0003).
5. The wear-resistant bright silver three-dimensional heat transfer film according to claim 2, characterized in that: In the preparation of tri(2,4,6-trimethylbenzoyl)germanium bromo, the equivalence ratio of potassium tri(2,4,6-trimethylbenzoyl)germanium to 1,2-dibromoethane is 5.5:
1.
6. The wear-resistant bright silver three-dimensional heat transfer film according to claim 5, characterized in that: In the preparation of potassium tri(2,4,6-trimethylbenzoyl)germanide, the molar ratio of tetra(trimethylsilyl)germanane: potassium tert-butoxide: 2,4,6-trimethylbenzoyl fluoride is 1:1:
3.
7. The wear-resistant bright silver three-dimensional heat transfer film according to claim 6, characterized in that: In the preparation of tetra(trimethylsilyl)germanane, the mass ratio of trimethylchlorosilane:lithium wire:germanium chloride is 69.4:10:31.
1.
8. The preparation process of a wear-resistant bright silver three-dimensional heat transfer film according to any one of claims 1-7, characterized in that: Includes the following steps: Step (1): Add acrylic resin to an organic solvent and stir until homogeneous to obtain a flowable liquid with a solid content of 25-30%. Coat the liquid onto the surface of a PET base film to obtain a release layer. The release layer has 70 coating lines and a wet coating weight of 6-8 g / m². 2 The dry coating weight is 1.6-1.8 g / m². 2 ; Step (2): Print the colored ink onto the surface of the release layer to obtain the colored printing layer; Step (3): Add poly(vinylidene fluoride-co-hexafluoropropylene) and dibutyl phthalate to acetone, heat to 50-55℃ and stir evenly. Coat the mixture on the surface of the color printing layer, air dry for 5-10 minutes, wash with anhydrous ethanol to obtain a porous resin substrate; add photoinitiator modified POSS filler to dimethyl carbonate, stir evenly, drop the mixture onto the porous resin substrate, air dry in the dark for 8-12 hours, purge with nitrogen for 10-15 minutes, and cure with ultraviolet light under nitrogen atmosphere for 10-15 minutes to obtain a protective layer; Step (4): Apply aluminum to the surface of the protective layer using a vacuum aluminum plating process, wash, air dry and let stand to obtain the aluminum plating layer; Step (5): Screen printing embossed varnish onto the surface of the aluminum-plated layer to obtain a screen-printed embossed layer; Step (6): Apply adhesive to the surface of the screen printing embossed layer to obtain an adhesive layer; finally, a heat transfer film is obtained.
9. The preparation process of a wear-resistant bright silver three-dimensional heat transfer film according to claim 8, characterized in that: In the preparation of the porous resin substrate, the mass ratio of poly(vinylidene fluoride-co-hexafluoropropylene): dibutyl phthalate is 1:(5-15).
10. The preparation process of a wear-resistant bright silver three-dimensional heat transfer film according to claim 8, characterized in that: During the preparation of the protective layer, the amount of photoinitiator-modified POSS filler added to the surface of the porous resin substrate was 3.22-3.46 g / m³. 2 .
Citation Information
Patent Citations
Abrasion-resistant non-trace silver-luster back sleeve glue heat transfer film and production process thereof
CN108543685A
POSS (Polyhedral Oligomeric Silsesquioxane) synthetic resin and preparation method thereof, POSS coating composition as well as preparation method and application thereof
CN117229508A